Metafiction and Social Commitment in Pynchon's V. - Luis Miguel García Mainar (Miscelánea: A Journal of English and American Studies)
The aim of this paper is to analyse Thomas Pynchon's V. within the tradition of metafictional literature, and to show that it proposes a new view of social commitment for the novel. The paper studies V. as a parody of reflexive literature in order to reveal that its reflexive nature emphasises the novel's incapacity to shape its material and bestow a truthful meaning on it. History, the act of narration, language's relationship with reality, the metaphorical and metonymical functions of language and mises-en-abyme are some of the strategies the novel parodies. Such reflexive mechanisms are refused the possibility of providing an integrating meaning. They are inscribed in a linguistic system whose processes of codification entail a trasformation and manipulation of reality. As a conclusion, the text proposes the absence of language as an alternative to a state of affairs which has been traditionally used by the dominant classes in order to oppress the rest of society.